To Some Questions About the Treatment of Diabetic Foot Syndrome in Patients with Covid-19 (Eurasian Medical Research Periodical, 2023)
Wound healing in diabetic foot syndrome is one of the serious problems in the treatment of patients with diabetes mellitus. Purulent-necrotic diseases of the foot are the most common cause of disability and death in patients with diabetes mellitus. Amputation of the lower limb is most often caused by the occurrence of ischemic gangrene, neuropathic ulcers, and the progressive development of necrosis and infection. This is due to the atypical course of the wound process in diabetes mellitus